2023
DOI: 10.1002/cssc.202202361
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of All‐Solid‐State Li‐ion Batteries: A Case Study of the Separation of Individual Components Within a System Composed of LTO, LLZTO and NMC**

Abstract: With the current global projection of over 130 million electric vehicles (EVs), there soon will be a need for battery waste management. Especially for all‐solid‐state lithium‐ion batteries (lithium ASSBs), aspects of waste management and circular economy have not been addressed so far. Within such ASSBs, the use of solid‐electrolytes like garnet‐type Li6.5La3Zr1.5Ta0.5O12 (LLZTO) may shift focus on strategies to recover not only the transition metal elements but also elements like La/Zr/Ta. In this work, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Another hydrometallurgical approach might be the selective acid leaching of individual components, in regard to the stability of different components and the possibility of complex formation. Waidha et al [115] in a second step. Furthermore, it was observed that all components maintained overall basic electrochemical activity.…”
Section: Oxide-based Ssbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another hydrometallurgical approach might be the selective acid leaching of individual components, in regard to the stability of different components and the possibility of complex formation. Waidha et al [115] in a second step. Furthermore, it was observed that all components maintained overall basic electrochemical activity.…”
Section: Oxide-based Ssbsmentioning
confidence: 99%
“…This can lead to an acidification of the aqueous solution, which will have an influence on the solubility of, e.g. cathode materials, such as phospho-olivine LiFePO 4 or the layered material Li(Ni,Co,Mn)O 2 , which already dissolves at moderate pH-levels [115]. We observed [146] that active cathode materials are partly dissolved when in contact with aqueous solutions of Li 3 InCl 6 , which results in contamination of the recrystallized Li 3 InCl 6 with transition metals and can change the conductivity of re-crystallized Li 3 InCl 6 significantly.…”
Section: Halide-based Ssbsmentioning
confidence: 99%
“…Longer Lifespan: The solid electrolytes in SSBs are less prone to degradation compared to liquid electrolytes, which tend to break down over time and under thermal stress [20,23]. This inherent stability of solid electrolytes contributes to a longer lifespan for SSBs, reducing the frequency of battery replacement and, in the long run, diminishing the environmental and economic impact of battery disposal [33].…”
Section: Advantages Relative To Conventional Battery Technologiesmentioning
confidence: 99%
“…Battery recycling represents a viable solution to these issues, promoting environmental protection and advancing sustainable manufacturing practices. Research and development efforts are underway to devise efficient and eco-friendly methods to reclaim lithium from SSBs, thus supporting the development of a circular economy for critical materials such as lithium [111][112][113].…”
Section: Case Studies and Real-world Examplesmentioning
confidence: 99%